Enhancing the Teaching of Digital Signal Processing through Project-Based Learning - Alqudah, Yazan; Qaralleh, Esam; Mace, Michelle (International Journal of Online and Biomedical Engineering (iJOE), 2013)
Engineering education is constantly challenged to bridge the gap between classroom and real world problems. This paper reports on the experience at PSUT to complement the teaching of digital signal processing through project-based learning. A low cost digital stethoscope is utilized by students to record heartbeat sounds and apply DSP concepts to extract vital information from the signal. The ability to apply concepts learned in the classroom to a real world problem was an important element that motivated students. The feedback from students reinforced the effectiveness of these techniques in teaching concepts of digital signal processing